(3GdhTGM aj ahGFO GdfcGMs - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B... (3abO CcKQ GdfGS ef GdJUfja aj af GdfcGM eG Hjf eSgH heNJUQ heSJhYH hebJUQ hYdi GdLedI aCMSf cJGH Cda aj Pdc heSJhYH dahGFO gPg GdeSGdc cJGH JMaI GdYQhS heJYI GdfahS dCHj YHO Gddg eMeO Hf CMeO GdJLGfj (B..s
(3BNQgG (B:s
... (3hef CeKGdge CZde ef JjS dfH MqeGf jbGd Gfg SaO SHYjf YfR aj SGYg bGdg CHh YeQh (B..(3? adeG CJi RhLJg aj GddjdI GdKGfjI bGd gPG MQ eYQha hGddg CYde , Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ddRQcdj (B3/301s
(3cTa GdXfhf dMGLj NdjaI (B2/2011s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs